Global population genetic structure and lineage differentiation of the stable fly, Stomoxys calcitrans - Tsai, Cheng‐Lung; Lu, Chia‐Ning; Tzeng, Hau‐You; Krafsur, Elliot S.; Tu, Wu‐Chun; Yeh, Wen‐Bin (Medical and veterinary entomology, 2023)
The bloodsucking fly, Stomoxys calcitrans (Diptera: Muscidae), is a cosmopolitan pest that transmits potential pathogens mechanically. We conduct phylogeographic analyses of S. calcitrans to resolve its global population genetic structure for establishing baseline of molecular studies. Results from mitochondrial gene suggested that the major divergence of S. calcitrans predominantly occurred 0.32–0.47 million years ago (Mya) and the subsequent diversifications took place during 0.13–0.27 Mya. The Ethiopian region was deduced as the most likely origin of S. calcitrans and the Nearctic lineages were considered to have originated from Oriental or Palaearctic regions. Our results further revealed that each biogeographic region of S. calcitrans likely maintains its genetic specialty, and yet, those non‐monophyletic relationships were possibly caused by ancestral retention, dispersal with mammals, long‐distance migration, and the international livestock industries. Moreover, the three highly diverged Ethiopian lineages may be putative cryptic species that require clarification of their veterinary importance. Unravelling the genetic structure of stable fly and preventing gene flow among biogeographic regions through anthropogenic activities are thus pivotal in livestock industry administration, particularly genetic exchange among differentiated lineages that might lead to the consequence of ecological trait alterations. Each biogeographic region of S. calcitrans maintains its genetic specialty. Ancestral retention, historical dispersal, long‐distance migration, and the international transportation shape the genetic structure of stable fly. Three highly diverged Ethiopian lineages are required to clarify their veterinary importance.